The Youth Olympic Games (Routledge research in sport, culture and society, 2014)
"The Youth Olympic Games The first summer Youth Olympic Games (YOG) were held in Singapore in 2010 and the first winter Youth Olympic Games in Innsbruck in 2012. The IOC hopes that the YOG will encourage young people to be more active and that they will bring the Olympic movement closer to its original founding values. This is the first book to be published on the Youth Olympic Games. It critically examines the origins of the Games and the motives of the Games organisers, as well as the organisation and management of the Games and their wider impact and significance. The first part of the book discusses the relationship between the YOG and the ideology of Olympism, in the context of broader developments in youth sport competitions. The second part investigates a wide range of managerial aspects including the bidding process, finance, the prominent role of young people on the organising committees and as volunteers, the role of media and sponsors, and the distinctive competition structure. The final part of the book assesses the current and likely future impact of the YOG on the host cities and countries, the IOC and on national youth sport policies. The Youth Olympic Games is essential reading for any researcher, advanced student or policy maker with an interest in Olympic Studies, sports development, sport policy, youth sport or event management"--Provided by publisher.